The use of GIS technology in the creation of local revitalisation programs as a tool for sustainable urban development - Marek, Ogryzek; Krzysztof, Rząsa (International Conference “Environmental Engineering”, 2017)
Revitalisation is a process of bringing degraded areas back from a state of crisis. It is carried out in a comprehensive way, through integrated activities for the local community, space and economy, concentrated territorially, led by revitalisation stakeholders and based on municipal (local) revitalisation programmes. The Municipal Council accepts the Revitalisation Programme in a resolution. It includes a detailed diagnosis of the revitalisation area, including an analysis of negative phenomena and local potentials in the area. Putting this purpose into practice makes use of GIS technology, which facilitates the process of gathering information about the area and preparing maps, and therefore is helpful to conduct urban inventories. GIS tools allow the location of concentrations of phenomena associated with the degradation of the urban space to be specified, such as crime, unemployment, areas where a large number of people have been excluded. These tools are helpful in indicating the development path for these areas. GIS tools can help find solutions to problem questions. They help justify the accepted solutions. Building multi-criteria decision-making models in a GIS environment, taking into account the social criteria, allows the revitalisation process of the area to proceed to fruition. The authors present the results of studies using the example of a local revitalisation programme in the City of Olsztyn.
Keywords: sustainable development; revitalisation; GIS